-3(-4x+2)=2(6x+1)

Simple and best practice solution for -3(-4x+2)=2(6x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-4x+2)=2(6x+1) equation:


Simplifying
-3(-4x + 2) = 2(6x + 1)

Reorder the terms:
-3(2 + -4x) = 2(6x + 1)
(2 * -3 + -4x * -3) = 2(6x + 1)
(-6 + 12x) = 2(6x + 1)

Reorder the terms:
-6 + 12x = 2(1 + 6x)
-6 + 12x = (1 * 2 + 6x * 2)
-6 + 12x = (2 + 12x)

Add '-12x' to each side of the equation.
-6 + 12x + -12x = 2 + 12x + -12x

Combine like terms: 12x + -12x = 0
-6 + 0 = 2 + 12x + -12x
-6 = 2 + 12x + -12x

Combine like terms: 12x + -12x = 0
-6 = 2 + 0
-6 = 2

Solving
-6 = 2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x^2-11x-152=0 | | -2x-35=-11 | | x-1=-2x+8 | | 4x^2-114=5x^2+25x | | 10+2x=6x-10 | | 5x+9+4x=18 | | 7x+44=-5 | | 3=2x+6x-5 | | 7(n-6)=3 | | 103=6x+3x+4 | | -4+3x+x=16 | | 2(7x+40)=4x-6(2-x)+7 | | 1=3x-4x+5 | | -6x+6+3x=18 | | 40=4x+x+10 | | 11=4x+5x-7 | | 86=7x+6x+8 | | 1+6x=71 | | (x/2)+4=10 | | -12=h/4 | | -9xy(-10xy)= | | 4k+mn=n-3form | | -5.5f=-66 | | 18(3)/6-18/6 | | 4X^4+36=40X^2 | | 62-7=6 | | -9=2.8+d | | -2x+7-2x=7 | | -10x=5x+5 | | 3x=2z-y | | (3x-5)=4 | | 49x=100x^2 |

Equations solver categories